KHOTBAH TENTANG DOSA DAN HUKUMAN: ANALISIS DAMPAK POSITIF DAN NEGATIF DALAM PESPEKTIF TEOLOGIS DAN PSIKOLOGIS - Martua Parluhutan Tamba; Joksan Simanjuntak; Dinda Artaulina Sidabutar; Yakub Pangihutan Silaban; Anderson Jordan Pakpahan; Enjel Capah; Samuel Nababan; Febri Walandari Marbun (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2026)
Sermons on sin and punishment are an important part of preaching God's Word in the church. However, a strong emphasis on sin and punishment often evokes various emotional responses in the congregation, such as guilt, fear, and even anxiety. This study aims to analyze the influence of sermons on sin and punishment on the psychological well-being of the congregation. The method used was descriptive qualitative research with a literature study approach, through analysis of books and journals on Christian theology and psychology. The results of the study indicate that sermons on sin and punishment can have a positive impact in the form of moral awareness and genuine repentance, but can also have negative impacts such as excessive guilt and psychological distress if delivered without a balance of love and hope. Therefore, preaching and communicating about sin and punishment in the congregation must be delivered wisely, while still emphasizing grace and restoration in Christ